PRODUCTIVITY AND ESTIMATED BREEDING VALUE OF THE DAIRY CATTLE GENE POOL IN THE REPUBLIC OF KAZAKHSTAN - Baimukanov Dastanbek Asylbekovich; Abugaliyev Serimbek Kurmanbaiuly; Seidaliyev Nurzhan Beskempirovich; Chindaliyev Askhat Erbosynovich; Dalibayev Ermek Kurmanbaevich; Zhamalov Bakbergen Seydakhanuly; Muka Shynar Bakytkyzy (Scientific Journal of Pedagogy and Economics, 2019)
With a linear estimation of the physique of first-calf heifers, it is established that in cows of domestic breeds, the parameters correspond to the optimal points of the species and the indicators of the extremities, but the parameters of the udder differ sharply. All the data on productive and exteriors were entered into the program of the Information and Analytical System (IAS), where the estimated breeding value of the studied cows was automatically calculated. The average estimated breeding value (EBV) for all breeds was 81.4. Among all breeds, the highest EBV level was determined in Holstein cows (84.3) of imported selection. The average milk yield of the studied herds per 1 cow was 5300± 30 kg of milk, with a mass fraction of fat of 3.74±0.02%, the mass fraction of protein of 3.16±0.01%, with a content of 324.7±23.8 thous. of somatic cells. The most productive were the cows of the Holstein breed, their productivity over the Alatau breed was 694 kg (P>0.99), over the black-and-motley breed it was1446 kg (P>0.999), over the Simmental breed it was 1982 kg (P>0.999), over the red steppe - 2038 kg (P>0.999), no significant difference was found in the content of fat and protein of cow. Somatic cells were within normal limits. When studying the dynamics of milk yields according to lactation, it is established that the milk productivity of the Alatau breed is characterized by growth (4844... 5679... 5458 kg) by the second-third lactation and gradual decrease (4716... 4017 kg) by the fifth. On average, for all lactations, cows of this breed brought 5123±275.4 kg. The dairy productivity of Holstein cows is increased by the fifth lactation, without recessions. On average, for cows of black and motley breed for all lactations, the milk yield was 4671±190 kg. Dynamics of milk yield of the Simmental breed increases from the first to the second lactation (3917... 4035 kg), in the third it decreases (4035... 3334 kg), from the fourth to the sixth lactation the sequence increases.